From Integration to Resilience: Rethinking Euro-Atlanticism in the Post-Ukraine European Order - Maksuti, Bekim (European Scientific Journal, ESJ, 2025)
The Russian invasion of Ukraine in 2022 reshaped European strategy, throwing back into the limelight questions over the character of Euro-Atlantic integration. For smaller states in particular, the post-Ukraine environment shows not just possibilities but also limitations to being joined together in a fight against external aggressor. The article argues that Euro-Atlanticism is transforming from a model focused on integrated institutions to one that stresses resilience-the ability of states and alliances to absorb shocks; adapt to a hybrid kind of threat; remain cohesive amid geopolitical uncertainty. Focusing on NATO and EU post-2022 evolution, it examines the way small states, particularly in the Western Balkans, manoeuvre the new balance between dependence on security and strategic independence. The analysis argues that the sustainability of the Euro-Atlantic order is the function, not just of external deterrence, but of internal political integrity, institutional trust and societal capacity.